Synthesis of Ga-doped Li7La3Zr2O12 solid electrolyte with high Li+ ion conductivity. Issue 2 (15th January 2021) - Huang, Xiao; Su, Jianmeng; Song, Zhen; Xiu, Tongping; Jin, Jun; Badding, Michael E.; Wen, Zhaoyin
Abstract: Garnet-type Li7 La3 Zr2 O12 (LLZO) Li + ion solid electrolyte is a promising candidate for next generation high-safety solid-state batteries. Ga-doped LLZO exhibits excellent Li + ion conductivity, higher than 1 × 10 −3 S cm −1 . In this research, the doping amount of Ga, the calcination temperature of Ga-LLZO primary powders, the sintering conditions and the evolution of grains are explored to demonstrate the optimum parameters to obtain a highly conductive ceramics reproducibly via conventional solid-state reaction methods under ambient air sintering atmosphere. Cubic LLZO phase is obtained for Li6.4 Ga0.2 La3 Zr2 O12 powder calcined at low temperature 850 °C. In addition, ceramic pellets sintered at 1100 °C for 320 min using this powder have relative densities higher than 94% and conductivities higher than 1.2 × 10 −3 S cm −1 at 25 °C.